The Role of Online Marketing Strategies and Influencer Marketing on Consumer Purchasing Decisions of the Forsgi Brand in East Jakarta - Rachmawati, Ninda (International Journal of Business, Law, and Education, 2026)
This study examines the influence of online marketing strategies and influencer marketing on consumer purchasing decisions of the Forsgi brand in East Jakarta. As digital platforms increasingly dominate marketing activities, businesses rely on online promotions and influencers to shape consumer behavior. This research employs a quantitative approach using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with data collected from 150 respondents who are familiar with or have purchased Forsgi products. The results indicate that online marketing strategies have a positive and significant effect on purchasing decisions. Influencer marketing also significantly influences purchasing decisions, particularly through credibility and trust. Simultaneously, both variables explain a substantial proportion of variance in consumer purchasing decisions. These findings highlight the importance of integrating effective online marketing strategies with influencer marketing to enhance consumer engagement and drive purchasing decisions, especially for local brands.